2008
DOI: 10.1124/jpet.108.141333
|View full text |Cite
|
Sign up to set email alerts
|

Niacin-induced “Flush” Involves Release of Prostaglandin D2from Mast Cells and Serotonin from Platelets: Evidence from Human Cells in Vitro and an Animal Model

Abstract: Niacin lowers serum cholesterol, low-density lipoprotein, and triglycerides, and it raises high-density lipoprotein. However, most patients experience cutaneous warmth and vasodilation (flush). Acetylsalicylic acid (ASA) can reduce this flush, presumably by decreasing prostaglandin D 2 (PGD 2 ) release from macrophages. Here, we show that methylnicotinate induces significant PGD 2 release from human mast cells and serotonin from human platelets. Intradermal injection of methylnicotinate induces rat skin vasodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 40 publications
2
30
0
2
Order By: Relevance
“…In mammalian organs, large amounts of PGD 2 are found only in the brain and in MC. Previous studies found MC-produced PGD 2 is the primary mediator of vasodilatation (the "niacin flush") after ingestion of niacin (nicotinic acid) [41]. Previously reported data reveals that non-IgE induced PGD 2 production was attenuated when ROS production was reduced (REF in comment).…”
Section: Discussionmentioning
confidence: 97%
“…In mammalian organs, large amounts of PGD 2 are found only in the brain and in MC. Previous studies found MC-produced PGD 2 is the primary mediator of vasodilatation (the "niacin flush") after ingestion of niacin (nicotinic acid) [41]. Previously reported data reveals that non-IgE induced PGD 2 production was attenuated when ROS production was reduced (REF in comment).…”
Section: Discussionmentioning
confidence: 97%
“…We recently showed that niacin induces serotonin release from platelets in a rat model (23). Serotonin has superficial vasodilatory actions (24), and elevated plasma serotonin levels (25) are associated with the facial flush characteristic of the Carcinoid syndrome (26).…”
Section: Discussionmentioning
confidence: 99%
“…Classical vasodilatory mediators, such as histamine, bradykinin, serotonin, and acetylcholine do undergo changes in their skin transudate levels after niacin challenge (Morrow et al, 1992;Plummer et al, 1977). However, Papaliodis et al (2008) showed that niacin induced the release of serotonin from human platelets in vitro and elevated blood levels of serotonin after intraperitoneal injection of niacin in rats. Although further study will be needed to clarify the possible role of serotonin, the vast majority of evidence points to a strongly predominant role of AA metabolites as primary mediators of the flush response to niacin.…”
Section: Mediation Of Niacin Flush By Aa Metabolitesmentioning
confidence: 99%